Interdisciplinary management of acute ischaemic stroke – current evidence on training requirements for endovascular stroke treatment. Position Paper from the ESC Council on Stroke and the European Association for Percutaneous Cardiovascular Interventions with the support of the European Board of Neurointervention: A step forward - Musialek, Piotr; Nizankowski, Rafal; Hopkins, L. Nelson; Micari, Antonio; Alejandro Alvarez, Carlos; N. Nikas, Dimitrios; Ruzsa, Zoltán; Luisa Kühn, Anna; Petrov, Ivo; Politi, Maria; Pilla, Sanjay; Papanagiotou, Panagiotis; et al. (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2021)
Stroke, a vascular disease of the brain, is the #1 cause of disability and a major cause of death worldwide. Stroke has a major negative impact on the life of stroke-affected individuals, their families and the society. A significant proportion of stroke victims indicate that would have preferred death over their after-stroke quality of life. Mechanical thrombectomy (MT), opening the occluded artery using mechanical aspiration or a thrombus-entrapment device, is a guideline-mandated (class I, level of evidence A) treatment modality in patients with large vessel occlusion stroke. MT clinical benefit magnitude indicates that a universal access to this treatment strategy should be the standard of care. Today there is a substantial geographic variation in MT deliverability, with large-scale disparities in MT implementation. In many countries effective access to MT remains severely limited. In addition, many of the MT-treated patients are treated too late for a good functional outcome because of logistic delays that include transportations to remotely located, scarce, comprehensive stroke centres. Position Paper from the European Society of Cardiology Council on Stroke and European Association for Percutaneous Cardiovascular Interventions on interdisciplinary management of acute ischaemic stroke, developed with the support of the European Board of Neurointervention fills an important gap in systematically enabling interventional cardiologists to support stroke intervention in the geographic areas of unmet needs in particular. We review strengths and weaknesses of the document, and suggest directions for the next steps that are swiftly needed to deliver MT to stroke patients more effectively.